Managerial style and bank loan contracting - Bill B. Francis; Iftekhar Hasan; Zhu Yun (Bank of Finland, 2013)
This paper provides direct evidence that managerial style is a key determinant of the firm's cost of capital, in the context of private debt contracting. Applying the novel empirical method by Abowd, Karmarz, and Margolis (1999) to a large sample that tracks job movement of top managers, we find that managerial style is a critical factor that explains a large part of the variation in loan contract terms. The loan-term-related managerial styles correlate with managerial styles of firm performance and corporate decisions, implying that certain managers achieve better firm performance via lower cost of capital and other desirable non-price loan terms. We further find direct evidence that banks "follow" managers' job changes and offer loan contracts with preferential terms to their new firms. Some of the preferred managerial styles reflect managers' personal characteristics, such as managerial ability, authority and conservatism
URN:NBN:fi:bof-20140807444
Keywords: 330